2023
DOI: 10.1002/jhm.13061
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing patients hospitalized without an acute care indication: A retrospective cohort study

Abstract: Background: Hospitalizations by patients who do not meet acute inpatient criteria are common and overburden healthcare systems. Studies have characterized these alternate levels of care (ALC) but have not delineated prolonged (pALC) versus short ALC (sALC) stays.Objective: To descriptively compare pALC and sALC hospitalizations-groups we hypothesize have unique needs.Designs, Settings, and Participants: A retrospective study of hospitalizations from March-April 2018 at an academic safety-net hospital.Main Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The mechanism to explain this finding is not within the of this study, though it has been previously identified that patients experiencing homelessness, those with self-pay or Medicaid funding, and those of racial/ethnic minorities are more likely to experience prolonged LOS. 7,15,[22][23][24][25] This is an important area for further study.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism to explain this finding is not within the of this study, though it has been previously identified that patients experiencing homelessness, those with self-pay or Medicaid funding, and those of racial/ethnic minorities are more likely to experience prolonged LOS. 7,15,[22][23][24][25] This is an important area for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with complex care needs often experience prolonged hospitalizations for non-acute reasons. 10 While numerous factors contribute to this dynamic, this frequently occurs because the patient lacks a safe or affordable placement option outside of the hospital. 11 Patients rarely prefer prolonged hospitalization, which is associated with serious health risks, including hospital-acquired complications, delirium, social isolation, depression, physical deconditioning, and loss of autonomy (e.g., hospital rules prohibiting patients from walking outside of the facility without permission).…”
Section: Role Of Mlps In Hospital-based Complex Care Initiativesmentioning
confidence: 99%
“…In this issue of the Journal , the characteristics of prolonged ALC (pALC) and short ALC (sALC) hospitalizations were compared based on a sample of adult patients 4 . ALC days accounted for approximately 20% of total inpatient days, while 10% of hospitalizations had pALC.…”
mentioning
confidence: 99%